Implementasi Metode SAW Pada Sistem Pendukung Keputusan Pemilihan Sales Terbaik - Stephen .; Mardiani Mardiani (Universitas Multi Data Palembang, 2026)
The sales evaluation process at PT Inti Bharu Mas currently relies on manual monitoring and Microsoft Excel, leading to slow processing, calculation errors, and a lack of transparency. These inefficiencies hinder management from making timely, objective decisions regarding employee performance and rewards. This study develops a web-based Decision Support System (DSS) using the Simple Additive Weighting (SAW) method to streamline evaluations. The system incorporates five key criteria: total sales, ordering outlets, visit frequency, service quality, and attendance. Developed using the Laravel framework, MySQL, and the Rational Unified Process (RUP) methodology, the system automates the ranking process. Results demonstrate that the DSS produces accurate, consistent sales rankings while significantly enhancing efficiency and transparency. By digitizing the evaluation workflow, PT Inti Bharu Mas ensures more objective managerial decision-making and provides a reliable basis for employee recognition and rewards through a more structured and automated approach.